Toll-Like Receptor 4 Mediated Oxidized Low-Density Lipoprotein-Induced Foam Cell Formation in Vascular Smooth Muscle Cells via Src and Sirt1/3 Pathway. (9th April 2021) - Chen, Zhongli; Xue, Qiqi; Cao, Lijuan; Wang, Yanpin; Chen, Yuanyuan; Zhang, Xiaojie; Xiao, Fan; Yang, Ying; Hayden, Melvin R.; Liu, Yan; Yang, Ke
Abstract : Oxidized low-density lipoprotein (oxLDL) induced a foam-cell-like phenotype of the vascular smooth muscle cells (VSMCs), leading to the inflammatory responses incorporating Toll-like receptor- (Tlr-) mediated cellular alterations. However, the role of Tlr4 in foam cell formation and underlying molecular pathways has not been comprehensively elucidated. To further investigate the mechanism, VSMCs were incubated with different doses of oxLDL, and then, the lipid, reactive oxygen species (ROS) accumulation, Tlr family genes, and the foam cell phenotype were explored. We observed that oxLDL induced foam cell-like phenotype in VSMCs and led to lipid and ROS accumulation in a dose-dependent manner. Furthermore, in the Tlr family, Tlr4 demonstrated the strongest upregulation under oxLDL stimulation. Simultaneously, oxLDL induced activation of Src, higher expression of Nox2, and lower expression of Mnsod, Sirt1, and Sirt3. By interfering the TLR4 expression, the phenotype alteration, lipid accumulation in VSMCs, and Src kinase activation induced by oxLDL were abolished. After interfering Src activation, the oxLDL-induced lipid accumulation and foam cell phenotype in VSMCs were also alleviated. Furthermore, the ROS accumulation, upregulated Nox2 expression, downregulated Sirt1, Sirt3, and Mnsod expression in VSMCs under oxLDL stimulation were also relieved after the knockdown of Tlr4. Additionally, overexpression of Sirt1 and Sirt3 ameliorated the ROS accumulation and foam cell-like marker expression in VSMCs. These results demonstrated that beyond its familiar role in regulating inflammation response, Tlr4 is a critical regulator in oxLDL-induced foam cell formation in VSMCs via regulating Src kinase activation as well as Sirt1 and Sirt3 expression.